FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN DAN STRUKTUR MODAL SEBAGAI VARIABEL MEDIASI - Melly Agnes; Widyasari Widyasari (Jurnal Paradigma Akuntansi, 2023)
The purpose of this study was to obtain empirical evidence regarding the effect of profitability and firm size on firm value with capital structure as a mediating variable. This study uses 93 samples, namely 31 companies in the consumer goods sector listedon the Indonesia Stock Exchange in 2018-2020.The results of the study show that profitability has a positive and insignificant effect on capital structure, firm size has a positive and significant effect on capital structure, profitability has a positive and significant effect on firm value, firm size has a negative and insignificant effect on firm value, capital structure has a negative and insignificant effect on firm value, and capital structure cannot mediate the relationship between profitability and firm size with firm value.